2016
DOI: 10.1074/mcp.m115.054296
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Plasma Proteome of Manduca sexta Larvae in Relation to the Transcriptome Variations after an Immune Challenge: Evidence for High Molecular Weight Immune Complex Formation

Abstract: Manduca sexta is a lepidopteran model widely used to study insect physiological processes, including innate immunity. In this study, we explored the proteomes of cellfree hemolymph from larvae injected with a sterile buffer (C for control) or a mixture of bacteria (I for induced). Of the 654 proteins identified, 70 showed 1.67 to >200-fold abundance increases after the immune challenge; 51 decreased to 0 -60% of the control levels. While there was no strong parallel between plasma protein levels and their tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 43 publications
5
39
0
Order By: Relevance
“…The ratios of HP1a and HP1b read numbers were 6.94 and 1.31 in hemocytes from the naïve and induced larvae, respectively. There was a 57% decrease in HP1a mRNA level in hemocytes and 17% decrease ( p < 0.05) in HP1a protein level in plasma after the immune challenge (He et al, 2016). In contrast, there was a 2.3-fold increase in HP1b mRNA and 17% increase ( p > 0.05) in HP1b protein.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ratios of HP1a and HP1b read numbers were 6.94 and 1.31 in hemocytes from the naïve and induced larvae, respectively. There was a 57% decrease in HP1a mRNA level in hemocytes and 17% decrease ( p < 0.05) in HP1a protein level in plasma after the immune challenge (He et al, 2016). In contrast, there was a 2.3-fold increase in HP1b mRNA and 17% increase ( p > 0.05) in HP1b protein.…”
Section: Resultsmentioning
confidence: 99%
“…These data agreed well with the developmental regulation in hemocytes. While the cross-reactivity of HP1a antibodies to HP1b made it impossible to distinguish the two proenzymes, quantitative proteomic analysis by nanoLC-MS/MS (He et al, 2016) allowed us to estimate that proHP1a was 8.8- and 6.3-fold higher in abundance than proHP1b in the naïve and induced day 3, 5 th instar larvae, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since fat body mRNA levels in general do not correlate well with their protein abundances in M. sexta plasma (He et al, 2016), we examined levels of the two serpins in hemolymph samples, each pooled from 2 or 3 insects. Serpin-9 level did not increase at 24 h after the immune challenge and decreased after M. luteus stimulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated changes in the hemolymph proteomes of fruit fly, silkworm, white butterfly, and tobacco hornworm in response to immune challenges 6,810 . In termites, Liu et al .…”
Section: Introductionmentioning
confidence: 99%